Targeting Angiotensin II Type-1 Receptor (AT1R) Inhibits the Harmful Phenotype of Plasmodium-Specific CD8+ T Cells during Blood-Stage Malaria - Silva-Filho, João L.; Caruso-Neves, Celso; Pinheiro, Ana A. S. (Frontiers in Cellular and Infection Microbiology, 2017)
CD8+ T-cell response is critical in the pathogenesis of cerebral malaria during blood-stage. Our group and other have been shown that angiotensin II (Ang II) and its receptor AT1 (AT1R), a key effector axis of renin-angiotensin system (RAS), have immune regulatory effects on T cells. Previously, we showed that inhibition of AT1R signaling protects mice against the lethal disease induced by P. berghei ANKA infection However, most of the Ang II/AT1R actions were characterized by using only pharmacological approaches, the effects of which may not always be due to a specific receptor blockade. In addition, the mechanisms of action of the AT1R in inducing the pathogenic activity of Plasmodium-specific CD8+ T cells during blood-stage were not determined. Here, we examined how angiotensin II/AT1R axis promotes the harmful response of Plasmodium-specific CD8+ T-cell during blood-stage by using genetic and pharmacological approaches. We evaluated the response of wild-type (WT) and AT1R–/– Plasmodium-specific CD8+ T cells in mice infected with a transgenic PbA lineage expressing ovalbumin; and in parallel infected mice receiving WT Plasmodium-specific CD8+ T cells were treated with losartan (AT1R antagonist) or captopril (ACE inhibitor). Both, AT1R−/− OT-I cells and WT OT-I cells from losartan- or captopril-treated mice showed lower expansion, reduced IL-2 production and IL-2R expression, lower activation (lower expression of CD69, CD44 and CD160) and lower exhaustion profiles. AT1R−/− OT-I cells also exhibit lower expression of the integrin LFA-1 and the chemokine receptors CCR5 and CXCR3, known to play a key role in the development of cerebral malaria. Moreover, AT1R−/− OT-I cells produce lower amounts of IFN-γ and TNF-α and show lower degranulation upon restimulation. In conclusion, our results show the pivotal mechanisms of AT1R-induced harmful phenotype of Plasmodium-specific CD8+ T cells during blood-stage malaria.